Evaluation Of Causes Of Bleeding Of Free Water From A Bentonite Slurry - Tony P. Suckling (Deep Foundations Institute, 2011)
This paper describes an investigation into the bleeding behaviour of bentonite slurry observed on a trial diaphragm wall panel. The bleeding is thought to be due to the bentonite experiencing a chemical reaction leading to settlement of the solids within the fluid, possibly as a self-weight consolidation process. The trial panel was constructed in a busy airport environment where many different chemical products are used for de-icing the aeroplanes, runways, apron areas, vehicle access and pedestrian routes. The relationships between slurry contamination, bleeding, bentonite hydration time and filter loss behaviour were examined as no relevant published literature could be found. The results show that the amount of bleed strongly depends on both the degree of contamination and the hydration time. It is concluded that bentonite fluids should be allowed to sit in the storage tank for at least 24 hours after mixing, and that the filter loss test is a quick and effective method to determine the potential for bleeding of contaminated slurries.